Community Perspectives On The Planning And Development Of Urban Conservation For The Inner City Of George Town, Penang - Tan, Sook Fern (2013)
The inner city of George Town, Penang has the earliest urban planning history in Malaysia and it has the largest number of pre-war (World War II) buildings in Southeast Asia. However, its urban conservation is not carried out comprehensively and effectively. There are gaps in the development direction of urban conservation between the government and the community. So this research aimed to find out the community perspectives on the planning and development of urban conservation in the inner city of George Town. By using grounded theory method, this research constantly compared and coded the community perspectives in the inner city of George Town. Substantive theory was discovered and translated into three standpoints that associated different economy values to urban conservation which affected the community’s attitudes and responses to the planning and the development of urban conservation, namely, the conservation purists, the centrists and the urban developmentalists. By reviewing and comparing the three theories, a localised urban conservation development model for George Town World Heritage Site aimed to conserve the pre-war buildings sustainably from the socio-economic aspects was developed.